1 - Madagascar : les forces armées garantes de la stabilité politique et démocratique ? - Juvence F. Ramasy (Identity, Culture and Politics, 2010)
No study of African politics can overlook the issue of the militarization of the state, as in many African countries armies played a key role in the aftermath of independence. Madagascar, for example, was ruled for over twenty years by the army. The army generally appears as a neutral entity which, as such, can guarantee the country’s political stability. However, there is no such thing as absolute neutrality, neither in Africa nor in western democracies. But the best hope for the army to become and remain as politically neutral as possible, is to demilitarize political power. Only the withdrawal of the military from politics and their subordination to civilian decisions do not suffice to ensure the army’s political neutrality. Such a withdrawal was carried out through the third wave of democratization. Yet these transitions followed the army’s directions. Democratization processes, then, cannot go without efforts towards neutralizing the military, and thus, towards demilitarizing the political society and depoliticizing the army. Post-transition regimes striving for democracy should bring about and preserve a formal separation of power between the political and the civilian spheres. For these regimes to establish a solid mandate, the army and the security apparatus need to be placed under democratic control. In Africa, the disengagement of the military from the public sphere came about with the political transitions of the 1990s. But with the current regime changes, this process seems to be challenged, as testifies the return of pretorianism in countries such as Mauritania, Guinea, Niger and Madagascar. Hence, demilitarizing politics, on the one hand, and depoliticizing and re‑professionalizing the army, on the other, remain essential issues to be addressed.